Pembelajaran Berkesadaran (Mindful Learning) Sebagai Strategi Peningkatan Kesejahteraan Psikologis Siswa dan Guru: Kajian Literatur - Yudi Biantoro; Sukiyanto Sukiyanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Mindful learning is a learning approach that emphasizes full presence and active awareness at every stage of the learning process. This approach does not focus solely on academic achievement but also plays an important role in enhancing the psychological well-being of both students and teachers. This study aims to examine mindful learning as an effective strategy for supporting psychological well-being in educational settings. This research employed a literature review method using a thematic analysis approach of fifteen key sources, including national and international journal articles as well as educational policy documents related to deep learning. The findings indicate that mindful learning strengthens executive functions, enhances self-control, supports emotional regulation, and fosters students’ intrinsic motivation and academic resilience. For teachers, its implementation contributes to stress reduction, increased empathy, and the creation of a positive and supportive classroom climate. Mindful learning is also aligned with the principles of deep learning in the Merdeka Curriculum, which emphasize meaning, awareness, and holistic student development. This approach serves as an essential foundation for creating an educational ecosystem that balances academic achievement with psychological well-being. Thus, mindful learning is not merely a pedagogical method but a foundational framework for building a healthy, reflective, and student-centered learning environment. The implications of this review highlight the need for continuous teacher training, the integration of mindfulness into the curriculum, and the strengthening of reflective practices in schools.